Sexual preference similarity, attitude similarity and perceived counselor credibility and attractiveness - Atkinson, Donald R.; Brady, Stephen; Casas, J. Manuel (Homosexuality and psychology, psychiatry and counseling)
"Donald R. Atkinson; Stephen Brady; J. Manuel Casas Fonds Suzan Daniel (FSD)"